Esthetic evaluation of different approaches to treat gingival recession associated with non-carious cervical lesion treatment: A 2-year follow-up - Santamaria, Mauro Pedrine; Mathias, Ingrid Fernandes; Fernandes Dias, Stephanie Botti; Neves Jardini, Maria Aparecida; Santamaria Junior, Milton; Sallum, Enilson Antonio (Mosher & Linder, Inc, 2014)
Purpose: To evaluate the esthetic outcome of four different approaches to treat gingival recession, associated with non-carious cervical lesion (combined defects) and the possible roles of patient-related factors in this esthetic outcome. Methods: 78 combined defects were previously treated by: coronally advanced flap (CAF), CAF plus cervical restoration using resin-modified glass-ionomer material (CAF+R), connective tissue graft (CTG) and CTG+R. After a follow-up of 2 years, esthetic evaluations were performed using a modification of the Root Coverage Esthetic Score (MIRES) and Qualitative Cosmetic Evaluation (QCE). Additionally, regression analyses were performed to evaluate the influence of patient-related factors in the final esthetic outcome. Results: The MRES showed that CAF and CTG had statistically significantly better results, when compared to the other groups (P<0.05). Similarly, the QCE showed that CAF and CTG, along with CAF+R presented better results, and CTG+R showed the poorest esthetic outcome. Regression analyses showed that the overall gingival inflammation (full mouth bleeding index - FMBI) was negatively associated with CTG MIRES score (P=0.04 and R=-0.48). This means that the greater the FMBI during the study period, the lower the final esthetic score.